Around the board : boards, platters, plates - Delaney, Emily (Dorling Kindersley, 2022)
With a chapter for Winter, Spring, Summer, and Fall, you'll learn to make nearly 50 creative, delicious boards that capitalize on the flavors and festivities of the season. Complete with suggested flavor and beverage pairings, styling tips, ingredient profiles, and more, Around the Board is your guide to year-round entertaining.